Midnight is the darkest hour : a novel - Winstead, Ashley (Sourcebooks Landmark, 2023)
"In her small hometown, librarian Ruth Cornier has always felt like an outsider, even as her beloved father rains fire-and-brimstone warnings from the pulpit at Holy Fire Baptist. Unfortunately for Ruth, the only things the townspeople fear more than the God and the Devil are the myths that haunt the area, like the story of the Low Man, a vampiric figure said to steal into sinners' bedrooms and kill them on moonless nights. When a skull is found deep in the swamp next to mysterious carved symbols, Bottom Springs is thrown into uproar--and Ruth realizes only she and Everett, an old friend with a dark past, have the power to comb the town's secret underbelly in search of true evil. A dark and powerful novel like fans have come to expect from Ashley Winstead, Midnight is the Darkest Hour is an examination of the ways we've come to expect love, religion, and stories to save us, the lengths we have to go to in order to take back power, and the monstrous work of being a girl in this world" --